2022
DOI: 10.1093/sleep/zsac070
|View full text |Cite
|
Sign up to set email alerts
|

Adverse driving behaviors are associated with sleep apnea severity and age in cognitively normal older adults at risk for Alzheimer’s disease

Abstract: Alzheimer disease (AD) pathology accumulates for decades before the onset of cognitive decline. Cognitively normal individuals with biomarker evidence of AD brain pathology (i.e., biomarker+ or preclinical AD) can be differentiated from individuals without AD brain pathology based on naturalistic driving data, such as hard acceleration or braking and speeding, measured using in-vehicle dataloggers. Older adults are at increased risk of injury and death from motor vehicle crashes and driving cessation is also l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 73 publications
2
18
0
Order By: Relevance
“…Very recently, Doherty et al, found that higher sleep apnea severity was associated with a higher incidence of adverse driving behavior, such as hard acceleration, braking and speeding. These findings were also observed in cognitively unimpaired old individuals [31].…”
Section: Pathophysiology Of Sleepiness At the Wheel In Osa Patientssupporting
confidence: 64%
See 1 more Smart Citation
“…Very recently, Doherty et al, found that higher sleep apnea severity was associated with a higher incidence of adverse driving behavior, such as hard acceleration, braking and speeding. These findings were also observed in cognitively unimpaired old individuals [31].…”
Section: Pathophysiology Of Sleepiness At the Wheel In Osa Patientssupporting
confidence: 64%
“…Another recent study was performed in older subjects to assess the effect of sleep apnea on driving behavior. OSA severity, measured by AHI, increased the likelihood of an adverse driving event, with a 1.25 times increase in the odds of an event for each eight-point increase in the AHI [31]. This is the first study that reported a "dose-effect" association between OSA severity and the risk of MVA.…”
Section: Epidemiology Of Driving Accidents In the General Population ...mentioning
confidence: 74%
“…These three measures were selected, as previous research has found differences in baseline measures of these behaviors between AD biomarker negative and biomarker positive groups, 18 and age-related differences in the incidence of these behaviors between negative and positive groups. 22 The variable was summarized and coded at a trip level, with "1" if there were any incidences of adverse driving behaviors, and "0" otherwise.…”
Section: Drivingmentioning
confidence: 99%
“…A better understanding of how preclinical AD affects the incidence of high‐risk, or “adverse,” driving behavior over time may inform clinicians on how early intervention can prolong safe driving in old age and maintain independence in both those who are at risk of developing AD and those wishing to age‐in‐place. A recent study into the effects of preclinical AD on adverse driving behaviors found an unexpected interaction between age and biomarker status 22 . Drivers with older age and preclinical AD biomarkers exhibited increased incidences of adverse driving compared to lower age ranges, whereas the opposite was true for biomarker‐negative individuals for whom age was associated with decreased driving risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation